2003
DOI: 10.1128/jcm.41.6.2483-2486.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of vanA and vanB Genes Directly from Clinical Specimens and Enrichment Broths by Real-Time Multiplex PCR Assay

Abstract: A real-time PCR assay previously developed for use on the Roche LightCycler platform was investigated as an alternative to culture for the direct detection of vancomycin-resistant enterococci (VRE) in clinical specimens. PCR primers and fluorescence resonance energy transfer hybridization probes specific for the vanA and vanB genes were combined in a multiplex real-time PCR assay performed directly with fecal material obtained by rectal swabbing and with enrichment broth samples. DNA was prepared from the rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 12 publications
1
51
0
3
Order By: Relevance
“…This has led to increased interest in screening of patients for colonization as well as to increased interest in methods used for a fast, sensitive, and reliable VRE detection (Vonberg et al, 2007). Rapid screening methods for VRE using direct polymerase chain reaction (PCR) from rectal swabs or stool have been described ( [Palladino et al, 2003], [Petrich et al, 1999] and [Satake et al, 1997]); some of these assays are commercially available ( [Bourdon et al, 2010], [Stamper et al, 2007], [Sloan et al, 2004] and [Usacheva et al, 2010]). These tests have been evaluated in a few studies performed, and excellent sensitivity and specificity for detecting vanA enterococci were shown, and a low specificity due to comparably high rates of supposed false-positive vanB samples appeared as a problem ( [Stamper et al, 2007] and [Sloan et al, 2004]).…”
Section: Introductionmentioning
confidence: 99%
“…This has led to increased interest in screening of patients for colonization as well as to increased interest in methods used for a fast, sensitive, and reliable VRE detection (Vonberg et al, 2007). Rapid screening methods for VRE using direct polymerase chain reaction (PCR) from rectal swabs or stool have been described ( [Palladino et al, 2003], [Petrich et al, 1999] and [Satake et al, 1997]); some of these assays are commercially available ( [Bourdon et al, 2010], [Stamper et al, 2007], [Sloan et al, 2004] and [Usacheva et al, 2010]). These tests have been evaluated in a few studies performed, and excellent sensitivity and specificity for detecting vanA enterococci were shown, and a low specificity due to comparably high rates of supposed false-positive vanB samples appeared as a problem ( [Stamper et al, 2007] and [Sloan et al, 2004]).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, vanA and vanB predominate and are the only two that are of epidemiologic importance due to the transmissibility of the resistance genes (2). The vanA and vanB genes are found almost exclusively in Enterococcus faecium and E. faecalis, the enterococcal species that most commonly cause disease in humans, but have been detected in other species of Enterococcus (16,32); and vanB has been detected in resident anaerobic flora of the human bowel (41a). VanA-mediated resistance is associated with inducible high-level resistance to vancomycin and teicoplanin, while vanB-mediated resistance is associated with resistance to vancomycin but retained susceptibility to teicoplanin.…”
Section: Detection Of Vre Directly From Patient Samplesmentioning
confidence: 99%
“…Our pediatric institution has a low prevalence of VRE, and we use conventional VRE screening methods, which require up to 5 days to identify VRE-positive patients (9) and 3 days to identify VREnegative patients. Other attempts to expedite VRE detection have included the use of 24-to 36-h selective broth cultures (9) and real-time PCR assays, using either swabs or broth for the identification of vanA and vanB genes encoding vancomycin resistance determinants (9,11). Preliminary work in our laboratory indicated that direct testing of rectal swabs with the Roche LightCycler VRE detection kit using DNA from our automated extraction protocol was inhibited in 50% of the samples tested.…”
mentioning
confidence: 99%